Molecular and physiological response of chives (Allium schoenoprasum) under different concentrations of selenium application by transcriptomic, metabolomic, and physiological approaches - Chen, Qiangwen (Plant physiology and biochemistry : PPB, 2025)
Copyright © 2025 Elsevier Masson SAS. All rights reserved.